Prose and Poetry through Time : Hebrew Verb Form Semantics in Zechariah - Huebscher, Stephen L. (Language and Linguistics E-Books Online, Collection 2024., 2025)
This is the first major study of the Biblical Hebrew verbal system of a prophetic book. It is also the first book-length study in over 60 years to focus on how genre affects the Hebrew verbal system. It advances a data-driven argument that Biblical Hebrew verb forms do not function one way in prose and another way in poetry. Lastly, the author addresses the diachronic development of Hebrew between the destruction of the First Temple and the writing of the Dead Sea Scrolls.